2013
DOI: 10.1017/s0305000913000019
|View full text |Cite
|
Sign up to set email alerts
|

How early do children understand gesture–speech combinations with iconic gestures?

Abstract: Children understand gesture+speech combinations in which a deictic gesture adds new information to the accompanying speech by age 1;6 (Morford & Goldin-Meadow, 1992; ‘push’+point at ball). This study explores how early children understand gesture+speech combinations in which an iconic gesture conveys additional information not found in the accompanying speech (e.g., ‘read’+BOOK gesture). Our analysis of two- to four-year-old children's responses in a gesture+speech comprehension task showed that children g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 23 publications
7
37
0
Order By: Relevance
“…Thus, these behavioral studies (e.g. Sekine et al, 2015;Stanfield et al, 2013) suggest that children between the ages three to five are gradually learning to comprehend information conveyed through gesture related to the co-occurring speech.…”
Section: Iconic Gesture Comprehension In Childrenmentioning
confidence: 98%
See 2 more Smart Citations
“…Thus, these behavioral studies (e.g. Sekine et al, 2015;Stanfield et al, 2013) suggest that children between the ages three to five are gradually learning to comprehend information conveyed through gesture related to the co-occurring speech.…”
Section: Iconic Gesture Comprehension In Childrenmentioning
confidence: 98%
“…Recent behavioral studies have shown that children gradually develop their ability to combine gestures with speech they hear as they get older (e.g. Broaders & Goldin-Meadow, 2010;Kelly & Church, 1998;McNeil et al, 2000;Sekine et al, 2015;Stanfield et al, 2013). For example, in Stanfield et al's (2013) study with children aged 2-4 years, an experimenter, sitting across from a child, said "I am eating" while simultaneously producing an iconic gesture depicting an action on an object (e.g.…”
Section: Iconic Gesture Comprehension In Childrenmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of gesture comprehension, at approximately age 2, children can interpret an iconic gesture as a label for an entity (Namy, Campbell, & Tomasello, 2004; Namy, 2008) or for an action (Goodrich & Hudson Kam, 2009; Marentette & Nicoladis, 2011), and can use iconic gestures produced by others to figure out the function of a novel toy (Novack, Goldin-Meadow, & Woodward, 2015). However, in many cases, children fail to robustly interpret others’ iconic gestures until ages 3 or 4, particularly when the gestures represent features of an entity, rather than an action (Stanfield, Williamson, & Özçalışkan, 2014; Tolar, Lederberg, Gokhale, & Tomasello, 2008). …”
Section: Introductionmentioning
confidence: 99%
“…In contrast, we expect a more protracted period for children to develop an understanding of empty‐handed movements as representational. Although some gestures such as points, are viewed as intentional and communicative before 2 years (Krehm, Onishi, & Vouloumanos, ; Woodward & Guajardo, ), being able to interpret the content of representational gestures appears to develop gradually between the ages of 2 and 5 years (Goodrich & Hudson Kam, ; Novack et al., ; Sekine, Sowden, & Kita, ; Stanfield, Williamson, & Ozcaliskan, ). For example, it is not until 26 months that children recognize the transparency of iconic gestures and find iconic representations easier to learn from than arbitrary representations (e.g., they find it easier to link a hammering motion with a hammer than to link an arbitrary motion with the hammer—before 26 months, the two representations for hammer are equally easy to learn; Namy, Campbell, & Tomasello, ).…”
mentioning
confidence: 99%